Maximum power point tracking of a solar PV array using single stage three phase inverter - Jayakumar, M; Vanitha, V; Jaisuriya, V; Karthikeyan, M; Daniel, George; Vignesh, T (International Journal of Engineering and Technology, 2018)
Solar power is widely available around the globe but efficient transfer of solar power to the load becomes a challenging task. There are various methods in which the power transfer can be done, the following work proposes a method for efficient tracking of solar power.Â MPPT [ maximum power point tracking] algorithm applied on three phase voltage source inverter connected to solar PV array with a three phase load. MPPT is applied on inverter rather than conventionally applying MPPT on DC-DC converter. Perturb and Observe method is applied in the MPPT algorithm to find the optimal modulation index for the inverter to transfer maximum power from the panel. Sine pulse width modulation technique is employed for controlling the switching pattern of the inverter. The algorithm is programmed for changing irradiation and temperature condition. The system does not oscillate about the MPP point as the algorithm set the system at MPP and does not vary till a variation in irradiation is sensed.Â The proposed system can be installed at all places and will reduce the cost, size and losses compared to conventional system.Â